2020
DOI: 10.1093/cvr/cvaa184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of icosapent ethyl on progression of coronary atherosclerosis in patients with elevated triglycerides on statin therapy: a prospective, placebo-controlled randomized trial (EVAPORATE): interim results

Abstract: Abstract Aims Though statin therapy is known to slow coronary atherosclerosis progression and reduce cardiovascular(CV) events, significant CV risk still remains. In the REDUCE-IT study, icosapent ethyl (IPE) added to statin therapy reduced initial CV events by 25% and total CV events by 30%, but its effects on coronary atherosclerosis progression have not yet been fully investigated. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 30 publications
(29 reference statements)
1
53
0
2
Order By: Relevance
“…A 9-month interim analysis of EVAPORATE showed that icosapent ethyl at 4 g/day did not reduce progression of low attenuation plaque volume (74% vs 94%; P =0.47) or fibrofatty plaque volume (87% vs 25%; P =0.65) versus placebo, respectively (n=30, IPE; n=37, placebo). 74 However, icosapent ethyl did reduce progression of total plaque versus placebo (15% vs 26%; P <0.001). The study is designed to conclude after 18 months of therapy.…”
Section: Omega-3 Fatty Acids and CV Riskmentioning
confidence: 93%
“…A 9-month interim analysis of EVAPORATE showed that icosapent ethyl at 4 g/day did not reduce progression of low attenuation plaque volume (74% vs 94%; P =0.47) or fibrofatty plaque volume (87% vs 25%; P =0.65) versus placebo, respectively (n=30, IPE; n=37, placebo). 74 However, icosapent ethyl did reduce progression of total plaque versus placebo (15% vs 26%; P <0.001). The study is designed to conclude after 18 months of therapy.…”
Section: Omega-3 Fatty Acids and CV Riskmentioning
confidence: 93%
“…In an ongoing trial, the EVAPORATE study, changes in coronary plaque, including low-attenuation, fibro-fatty, fibrous, calcified and non-calcified plaque, over a period of 9 to 18 months are being examined in patients treated with statins plus a higher dose of EPA, 4 g/day [11]. The results of interim analysis at nine months, which were presented in 2019 AHA Scientific Sessions (Philadelphia, PA), indicated slowed progression of calcified plaque: EPA, 1% decrease vs. placebo, 9% increase, p = 0.001 [126]. These clinical studies were summarized in Table 2.…”
Section: Effects Of Epa On Arterial Calcification In Clinical Studiesmentioning
confidence: 99%
“…New drugs, such as bempedoic acid, a small molecule that inhibits cholesterol synthesis [9], or inclisiran, a new anti-PCSK9 operating as a synthetic small interfering ribonucleic acid (siRNA), are currently being evaluated as additional weapons to be added to our armamentarium [10]. Beyond LDL lowering drugs, anti-inflammatory drugs such as colchicine [11,12], and purified omega 3 fatty acids [13] may add plaque-stabilizing effects, by modifying low-attenuation plaque components, as shown by recent CCTA studies [14,15]. CCTA features suggestive of high-risk individuals for future ACS and sudden death, along with targeted pharmacologic options for plaque stabilization, are summarized in Fig.…”
mentioning
confidence: 99%